Taboo Words Used in Pedawa Village Related to Tri Hita Karana - Prayoga, Gusti Km Arysuta; Budasi, I Gede; Mahendrayana, Gede (STKIP AGAMA HINDU SINGARAJA, 2024)
In this research, an examination was conducted on the use of taboo words, specifically in the Balinese language, within Pedawa Village. The primary aim of this investigation is to uncover the instances of taboo words employed in the three harmonious concepts of life (Tri Hita Karana). The study is situated in Pedawa Village, Buleleng. Consequently, a descriptive qualitative method was employed in the research design. The main tools utilized in the study were the researcher as the principal instrument and an interview guide. Data collection involved in-depth interviews, and three informants were selected during these sessions as the primary data sources. The findings of the study revealed a total of sixty-eight (68) instances of taboo words being used. This outcome underscores that the residents of Pedawa Village persist in utilizing taboo words in the Balinese language as a means of preserving their cultural heritage.